Penanaman Pendidikan Karakter Religius dan Peduli Lingkungan di SMP IT Assalam - Dina Purnama Sari; Deasy Arisanty; Herry Porda Nugroho Putro (Universitas Lambung Mangkurat, 2022)
The cultivation of religious characters and care for the environment is a character that must be instilled in every student, to support behavior that is in accordance with the motto of the SMP IT Assalam Pelaihari which is